Research Trends on Creative Thinking Skills in Indonesian Applied Linguistics Journals: Insights from Research Designs to Data Analysis - Munibi, Ahmad Zaki; Rafli, Zainal; Murtadho, Fathiaty (Institut Agama Islam Negeri Palopo, 2024)
Fostering creative thinking skills is a crucial objective within 21st-century education. This research applied content analysis to several articles published in Indonesian Applied Linguistics journals between 2014 and 2024, focusing on creative thinking as the central theme. The findings indicate a notable increase in the number of publications emphasizing creative thinking over the past four years, with qualitative research being the predominant methodology. Undergraduate students were the most frequently studied population, and a variety of materials were utilized in the research spanning the last decade. Questionnaires were the most commonly employed data collection tool, while thematic analysis was the most frequently used method for data interpretation. Based on these findings, several recommendations are offered for future research on creative thinking skills, including expanding the range of research designs and employing more refined data analysis techniques.